Synthesis of thymidine phosphorylase inhibitor based on quinoxaline derivatives and their molecular docking study - Noor Barak, Almandil; Taha, Muhammad; Farooq, Rai Khalid; Alhibshi, Amani; Ibrahim, Mohamed; Anouar, El Hassane; Gollapalli, Mohammed; Rahim, Fazal; Nawaz, Muhammad; ,, Syed Adnan Ali Shah; Ahmed, Qamar Uddin; Zakaria, Zainul Amiruddin (MDPI, 2019)
We have synthesized quinoxaline analogs (1–25), characterized by 1H-NMR and HREI-MS and evaluated for thymidine phosphorylase inhibition. Among the series, nineteen analogs showed better inhibition when compared with the standard inhibitor 7-Deazaxanthine (IC50 = 38.68 ± 4.42 µM). The most potent compound among the series is analog 25 with IC50 value 3.20 ± 0.10 µM. Sixteen analogs 1, 2, 3, 4, 5, 6, 7, 12, 13, 14, 15, 16, 17, 18, 21 and 24 showed outstanding inhibition which is many folds better than the standard 7-Deazaxanthine. Two analogs 8 and 9 showed moderate inhibition. A structure-activity relationship has been established mainly based upon the substitution pattern on the phenyl ring. The binding interactions of the active compounds were confirmed through molecular docking studies.